2013
DOI: 10.1186/2196-1042-14-38
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of interradicular bone density in the maxilla and mandible: implications in clinical orthodontics

Abstract: BackgroundBone density at the interradicular area plays an important role during orthodontic treatment. In view of this fact, the study was designed to quantitatively evaluate the bone density at the interradicular areas of the alveolar and basal bones of maxilla and mandible by computed tomography.MethodsOne hundred and nine computed tomographic images were randomly selected, and bone density was measured in Hounsfield units (HU) with bone mineral density software (Siemens VA20A_SP3A). The sample consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…Owing to mechanical and anatomic difficulties, implant treatment in the atrophic maxilla represents a challenge. The trabecular compartment of the canine/premolar region offered higher quality when compared with the posterior maxilla and the basal bone showed a higher density than the alveolar bone 45 . So, in implant rehabilitations, clinicians should consider the amount of cortical bone around the nasal cavity in order to get more implant stability 46 .…”
Section: Discussionmentioning
confidence: 95%
“…Owing to mechanical and anatomic difficulties, implant treatment in the atrophic maxilla represents a challenge. The trabecular compartment of the canine/premolar region offered higher quality when compared with the posterior maxilla and the basal bone showed a higher density than the alveolar bone 45 . So, in implant rehabilitations, clinicians should consider the amount of cortical bone around the nasal cavity in order to get more implant stability 46 .…”
Section: Discussionmentioning
confidence: 95%
“…According to Madhupura et al [28] and Masahiro Iijima [30], the implant of 8 mm × 1.3 mm is placed because longer miniscrew implants were associated with a greater incidence of sinus and bi-cortical perforations. According to Tina Chugh et al [37], the highest cortical bone density was observed between the second premolar and first molar. So, the implant was placed at the second premolar and first molar regions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicate that there were no significant differences between both sides for all measured variables for both genders. Human studies showed no difference in bone densities between left and right sides (3,8,13,(14)(15)(16)(17) . This investigation found no significant gender differences in buccal and palatal cortical bone density which is in accordance with others (3,8,13,16 17) .…”
Section: Discussionmentioning
confidence: 99%